Secondary Arc Extinction in Extra High Voltage Systems Using Grounding Switches - Qais M. Alias; Wafaa F. Tobia (Diyala Journal of Engineering Sciences, 2014)
Long Extra High Voltage (EHV) transmission systems tend to bring a pronounced state of secondary arcing. Therefore, an essential pre-requisite for single-phase-switching application, is the possibility and speed of secondary arc final extinction during suitably short dead-time. During the past several decades, many techniques had been proposed and implemented in order to ensure fast secondary arc extinction. Among these was the use of High Speed Grounding Switches (HSGS’s). In such technique, the faulted phase is grounded via special switches; one at each end of the EHV line after the fault is cleared by both line ends circuit breakers. The primary advantage of grounding the faulted phase is the reduction of the fault point recovery voltage to a very low value. This, coupled with the circulation of opposite loop currents in the fault path, reduces the secondary arc current and lead to a fast secondary arc extinction. A sample 500kV, 300km transmission system equipped with High Speed Grounding Switches is modeled as a test system. The modified Fourier transform is used to calculate the system response through, fault, fault clearance, HSGS’s operation, and line restoration. The non-linearity of the secondary arcing state is also accounted for. The paper concludes with a presentation of some computational results related to the above mentioned EHV system showing that HSGS’s greatly improves the single-phase-switching performance.